Development and Analysis of Automatic Controls of Washer and Hand Dryer Equipment - Satrio Wicaksono, Alfiansyah; Tjahjanti, Prantasi Harmi (International Journal on Human-Computing Studies, 2025)
The results of making and testing hand washing and drying equipment are technological changes and improvements that are useful in everyday life and can even reduce the spread or transmission of viruses. When using hand washing and hand drying equipment, you no longer need to hold/press/squeeze the equipment, you only need to bring your hand closer to the equipment, you can clean your hands in a short time and it is also more practical.